Analysis of FKIP Students' Perception Towards The Implementation of The PjBL Model In Improving Creativity and Learning Independence - Wahidah, Nina Ikhwati; Iskandar, Iskandar; Pixyoriza, Pixyoriza (JUPE : Jurnal Pendidikan Mandala, 2025)
In the era of 21st century education, a learning approach that can encourage creativity and learning independence is needed to prepare students to face global challenges. One of the learning models that is considered effective in this context is Project Based Learning (PjBL). This study aims to analyze the perceptions of FKIP students towards the implementation of the PjBL model and its impact on increasing creativity and learning independence. The method used in this study is a quantitative survey method with a descriptive and correlational approach. A sample of 100 students was selected by simple random sampling. The results showed that the majority of students had a positive perception of the implementation of PjBL (76% in the "good" and "very good" categories). As many as 73% of students showed a high level of creativity, and 69% showed high learning independence after participating in project-based learning. The correlation test showed a significant relationship between perceptions of PjBL and creativity (r = 0.642) and learning independence (r = 0.598). Regression analysis showed that perceptions of PjBL contributed 41.2% to creativity and 35.7% to learning independence. This shows that PjBL provides a meaningful learning experience, fosters creative thinking skills, and increases student independence in managing the learning process. These findings are supported by various recent studies that show the effectiveness of PjBL in developing essential 21st century skills. Therefore, this model deserves to be adopted more widely in learning in higher education.